Transformation in Higher Education
XII, 322 p.
Keywords: This book presents the most comprehensive and most thorough study of the developments in South African higher education and research after the first democratic elections of 1994 – that is of post-Apartheid South African higher education. This volume will provide its readers with a detailed insight into the new (i.e. post-1994) South African higher education system. The large number of experienced authors and editors involved in the book guarantees that the reader will be introduced in the new SA higher education system from a large number of perspectives that are presented in a consistent and coherent way. This book will be of interest to scholars, students, administrators, policymakers and politicians interested in South Africa, higher education and research, and policy analysis. "Publications on higher education are not new. But this volume, which is the first of its kind as a collective effort of tracing and examining the twists and turns taken by processes of change in the South African higher education system in a context of profound societal and global transformation, adds a fresh dimension to the debate. In its examination of the extent to which the changes were in line with policy intentions, particularly with regard to equity, democratisation, responsiveness and efficiency, and how a new institutional landscape started emerging, it makes a momentous contribution to the current debate about higher education restructuring." Njabulo Ndebele, Vice-chancellor, University of Cape Town and Chair of the South African Association of University Vice-chancellors "This book addresses a rich variety of issues on South African higher education. It puts these in the relevant context of the process of globalization and it shows that the South African experiences offer us a lot to learn. Highly recommended for those who are intrigued by the innovations taking place in South African highereducation as well as for those who intend to grasp the effects of globalization." Frans van Vught, Rector Magnificus and founding Director of the Center for Higher Education Policy Studies, University of Twente, The Netherlands "Reflection is a crucial ingredient to learning. In this book on higher education we have reflections on a unique period in the history of a country that managed its transition to democracy in a way that was unique, but from which we can all learn. Higher education in South Africa played a vital role in that transition and was part of the many tensions, choices and influences. They have been thoughtfully captured." Brenda Gourley, Vice-chancellor, The Open University, UK and board member, Centre for Higher Education Transformation. "No contemporary higher education system has changed as dramatically as that in South Africa. This book, rich in data, examines the changes that took place and offers insights into how change frequently cannot be predicted. The analysis captures the excitement, high expectations, remarkable successes, and failures in the transformation of the apartheid system of higher education. This excellent study provides rich fare for comparative analysis." Fred M. Hayward, American Council on Education Pilot Project, Executive Vice President, Council for Higher Education Accreditation, US.